Between Empathy and Solidarity. How Civic Activism Inhabits the Boundaries of Europe and Citizenship on Social Media Platforms - Battisti, Fabiana; Bruno, Marco (PARTECIPAZIONE E CONFLITTO, 2023)
This study explores the potential of digital civic activism, considering the existing contributions of migration, political, social movements, and media studies on solidarity towards contemporary migration flows in Europe. The study investigates how the unbalanced techno-symbolic assemblage of power exercised on European borders can be challenged through spontaneous acts of online solidarity. It looks at bottom-up solidarity on social media platforms, holding together two dimensions: the communicative practices of specific singular makers of solidarity, seen as potential activation elements; the response of the users reached and involved by their content. To this end, two activists located on the real borders of the Balkan route and on the digital borders of the social media platform Facebook have been studied, namely Nawal Soufi and Lorena Fornasir. A quali-quantitative analysis was carried out on posts and related comments published in the last two years on the Facebook pages of the two activists. We argue that in today's fragmented digital public sphere, their communicative practices are acts of citizenship insofar as they represent a form of resistance to the European fortress system and re-appropriation of the use of social media. Indeed, they can empathically - emotionally and cognitively - connect networked citizens to the reality of migration flows, conveying awareness and soliciting the participation of a possible mediapolis that casts on/offline acts.